Transumbilical Thoracoscopy Versus Conventional Thoracoscopy for Lung Wedge Resection: Safety and Efficacy in a Live Canine Model. (December 2015) - Chen, Tzu-Ping; Yen-Chu,; Wu, Yi-Cheng; Yeh, Chi-Ju; Liu, Chien-Ying; Hsieh, Ming-Ju; Yuan, Hsu-Chia; Ko, Po-Jen; Liu, Yun-Hen
Purpose . Transumbilical single-port surgery has been associated with less postoperative pain and offers better cosmetic outcomes than conventional 3-port laparoscopic surgery. This study compares the safety and efficacy of transumbilical thoracoscopy and conventional thoracoscopy for lung wedge resection. Methods . The animals (n = 16) were randomly assigned to the transumbilical thoracoscopic approach group (n = 8) or conventional thoracoscopic approach group (n = 8). Transumbilical lung resection was performed via an umbilical incision and a diaphragmatic incision. In the conventional thoracoscopic group, lung resection was completed through a thoracic incision. For both procedures, we compared the surgical outcomes, for example, operating time and operative complications; physiologic parameters, for example, respiratory rate and body temperature; inflammatory parameters, for example, white blood cell count; and pulmonary parameters, for example, arterial blood gas levels. The animals were euthanized 2 weeks after the surgery for gross and histologic evaluations. Results . The lung wedge resection was successfully performed in all animals. There was no significant difference in the mean operating times or complications between the transumbilical and the conventional thoracoscopic approach groups. With regard to the physiologic impact of the surgeries, the transumbilical approach was associated with significant elevations in body temperature on postoperative day 1, when compared with the standard thoracoscopic approach. Conclusions . This study suggests that both approaches for performing lung wedge resection were comparable in efficacy and postoperative complications.